What is the alternative to persistent therapy? The English proposal for standardized procedures applied in the last hours of the oncological patient’s life - Bochenek, Justyna; Püsküllüoğlu, Mirosława; Stochel-Gaudyn, Anna (Contemporary Oncology/Współczesna Onkologia, 2011)
Liverpool Care of Dying Pathway (LCP) is a protocol that standardizes the quality of care for dying patients and their families as well as helping to discontinue inappropriate medical interventions, particularly in hospitals and hospices. Developed in the UK, it was originally designed for cancer patients, but was quickly adapted for other groups of patients. LCP is designed to provide high quality medical, psychological and spiritual care to the dying patient. It is one of several such protocols commonly used throughout the world. This article presents a description of the pathway, its origin and use as well as the proposal to include it in the Polish standards.